Optimization of quercetin loaded palm oil ester based nanoemulsion formulation for pulmonary delivery - Arbain, Noor Hafizah; Salim, Norazlinaliza; Wui, Wong Tin; Basri, Mahiran; Abdul Rahman, Mohd Basyaruddin (Japan Oil Chemists' Society, 2018)
In this research, the palm oil ester (POE)- based nanoemulsion formulation containing quercetin for pulmonary delivery was developed. The nanoemulsion formulation was prepared by high energy emulsification method and then further optimized using D-optimal mixture design. The concentration effects of the mixture of POE:ricinoleic acid (RC), ratio 1:1 (1.50-4.50 wt.%), lecithin (1.50-2.50 wt.%), Tween 80 (0.50-1.00 wt.%), glycerol (1.50-3.00 wt.%), and water (88.0-94.9 wt.%) towards the droplet size were investigated. The results showed that the optimum formulation with 1.50 wt.% POE:RC, 1.50 wt.% lecithin, 1.50 wt.% Tween 80, 1.50 wt.% glycerol and 93.90 % water was obtained. The droplet size, polydispersity index (PDI) and zeta potential of the optimized formulation were 110.3 nm, 0.290 and －37.7 mV, respectively. The formulation also exhibited good stability against storage at 4℃ for 90 days. In vitro aerosols delivery evaluation showed that the aerosols output, aerosols rate and median mass aerodynamic diameter of the optimized nanoemulsion were 99.31%, 0.19 g/min and 4.25 µm, respectively. The characterization of physical properties and efficiency for aerosols delivery results suggest that POE- based nanoemulsion containing quercetin has the potential to be used for pulmonary delivery specifically for lung cancer treatment.